Multicultural Education on Student Character Formation - Mirta Pakambanan; Sulpiani; A.Oktamaya Tenri Awaru (PT FORMOSA CENDEKIA GLOBAL, 2023)
The realization of multicultural education is not just for students to get material at school, but students must also be able to experience multicultural practice directly. Thus, teachers, principals, school staff, employees and security guards must be able to create a multicultural atmosphere in schools. And, multicultural education should not only be obtained during formal education, but non-formal and informal education must also apply a multicultural system. This study uses library research where data is taken from books, journals and relevant themes. This research resulted in the internalization of multicultural education on integral aspects of student subjects. Internalized values ​​must contain elements of tolerance and mutual cooperation so that people can respect each other.